Three-dimensional X-ray diffraction imaging of dislocations in polycrystalline metals under tensile loading - Mathew J. Cherukara (Nature Portfolio, 2018)
Identifying atomic defects during deformation is crucial to understand material response but remains challenging in three dimensions. Here, the authors couple X-ray Bragg coherent diffraction imaging and atomistic simulations to correlate a strain field to a screw dislocation in a single copper grain.